Manajemen Kearsipan Dalam Menunjang Kegiatan Administrasi di SMKN 2 Ponorogo - Elin Anisa Dilla; Wilis Werdiningsih (Southeast Asian Journal of Islamic Education Management, 2023)
In implementing school activities, archive management is a source of information in planning, organizing and evaluating which will be used as a guide in decision making. Archives management influences administrative activities in the administrative sector. With good archives management, it will be easier for the school to obtain the necessary archives through the administration sector. In managing archives, SMKN 2 Ponorogo has special administrative staff. Archives are neatly arranged with clearly written codes, which makes it easier for administrative members when they need archives when needed. The objectives of the research are: 1) to understand the stages of archive creation and management; 2) know the stages of use and maintenance of archives; 3) as well as knowing the stages of determining the final fate of archives in supporting administrative activities in the administrative sector at SMKN 2 Ponorogo. This research uses a qualitative approach. Data collection through in-depth interviews, documentation and observation. Data analysis uses a data condensation model, data presentation, and drawing conclusions. Based on data analysis, the following results were found: 1) The archive creation stage was carried out by internal and external parties. Meanwhile, archive management is directly carried out by the TU department; 2) All parties are allowed to use the archives at SMKN 2 Ponorogo but must be intermediary with TU staff. Meanwhile, archive maintenance is carried out using an archive storage system, namely soft file and hard file storage; 3) Stage of determining the final fate of the archive. If archives are still needed they will be saved, but for archives that are not needed they will be burned; 4) With archive management, the archives in the administration section are more organized and neatly stored so that at any time the archives are needed easily.